دراسة تعبير المورثة 11-KMP في الليشمانيا المدارية L. tropica بطوريها أمامي وعديم السوط - مرعي, مؤيد; سكرية, شادي; عبادي, عبد القادر (Latakia University Journal -Biological Sciences Series, 2014)
يعد البروتين الغشائي لمنشأ الحركة-11 (KMP-11)، الموجود في جميع وحيدات الخلية ذات الأسواط المدروسة إلى الآن، مرشحاً محتملاً ليكون لقاحاً ضد داء الليشمانيات. إذ أن الجزيئة المرشحة لتكون لقاحاً مناسباً ضد داء الليشمانيات يجب أن يعبر عنها في عديمات السوط، الأشكال المخمجة للثدييات. إلا أن التعبير عن KMP-11 في عديمات السوط ما يزال موضع جدل. في هذه الدراسة، قمنا أولاً بعزل وزراعة وتنميط عينة من الليشمانيا المدارية L. tropica، ومن ثم قمنا بدراسة التعبير عنKMP-11 في أماميات السوط وفي عديمات السوط لطفيلي هذه السلالة بوساطة تقانة RT-PCR مستخدمين شفعاً من البادئات النوعية. أظهرت النتائج أن RNA الرسول للمورثة KMP-11 موجود في أماميات وعديمات السوط من الليشمانيا المدارية. يتوافق التعبير عن هذه الجزيئة في عديمات السوط مع قدرة الحماية المناعية التي أظهرها سابقاً لقاح DNA تجريبي يقوم على المورثة KMP-11، كما ويتوافق مع حدوث استجابة مناعية خلطية وخلوية الوساطة اتجاه البروتين KMP-11 في الحيوانات المصابة بالليشمانيا. Kinetoplastid membrane protein-11 (KMP-11), a protein present in all kinetoplastid protozoa studied up to date, is considered a potential vaccine candidate for Leishmaniasis. Such vaccine molecules must be expressed in amastigotes which represent the infective forms for mammals, while promastigotes are the flagellate forms found in the insect hosts. However, the expression of KMP-11 in amastigotes is still a subject of controversy. In this study, a strain of L. tropica was isolated, cultivated, and genotyped. The expression of KMP-11 gene in this strain was evaluated in promastigotes and in amastigotes by RT-PCR using specific primer pairs. The results proved the presence of mRNA of KMP-11 in both promastigotes and amastigotes forms of L. tropica. The expression of this molecule in amastigotes is consistent with the previously demonstrated immunoprotective capacity of KMP-11 DNA vaccine as well as the presence of humoral and cellular immune responses against KMP-11 in Leishmania-infected animals.